Mandating a Culture of Service: Pro Bono in the Law School Curriculum - Les A McCrimmon (Legal Education Review)
An important educational issue in legal higher education is the integration of skills into the undergraduate curriculum.1 This raises a whole series of questions including: What are these skills? Which skills reach across disciplines? Which are discipline specific? How essential are they and how can they be taught?2 Integral to this issue is that students in the post modern 21st century are continuously challenged by unique situations which are ill-defined, for which they may have no previous experience and which do not necessarily have one clear solution. Such divergent problems are not quantifiable or verifiable and so do not lend themselves to a single, simple solution3 but require a self-directed response based on a creative analysis of the contextual factors involved. Problem-based learning (PBL), with its emphasis on autonomy and collaborative, active learning, appears to be one way to encourage students, particularly first years, to develop the skills needed to deal with the dynamic complexity4 with which they are increasingly confronted. In particular, the author argues in this article, it is an approach that is effective in teaching the skill of legal problem solving. This article describes the process undertaken to develop a computer-based module designed to introduce law students, through the use of PBL, to legal problem solving and its potential relevance to their professional practice. Further, the article discusses how the principles and processes of PBL as integrated into a computer-based education module (CBE) can be applied to legal problem solving. It describes the use of the module with first year off-campus students studying law at the Queensland University of Technology (QUT) as well as final year on-campus law students and demonstrates how the CBE module has been integrated into teaching legal problem solving skills for these students.